GROWTH RESPONSE AND BIOCHEMICAL CHANGES IN WISTAR RATS FED ON MIXED SPICESSUPPLEMENTED DIET - Idoko, A. S.; Zaharaddeen, A. S.; Mohammad, F.; Nwabuike, G. C.; Oyolola, O. S.; Ahmed, H. (FUDMA JOURNAL OF SCIENCES, 2023)
The research was conducted to study the growth and biochemical changes in Wistar rats fed on mixed spices-supplemented diet. Syzygium aromaticum, Zingiber officinale, Allium sativum and Allium cepa were dried, pulverized and mixed in the ratio of 1:2:2:2 respectively. Eight Wistar albino rats (81.60±17.80 g) were divided into two groups of four rats each with nearly equal average weight and randomly assigned to two experimental diets; diet A (control) was starters` mash while diet B was 1.5% mixed spices of starters` mash. The rats were maintained on their respective diets ad libitum for six weeks after one week of acclimatization. The feed intake, change in body weight, feed conversion ratio, fasting blood glucose, haematological and lipid profiles, and serum transaminase activities were determined using standard methods. The results showed that the feed consumed (113.4±3.39 g), feed conversion ratio (7.17±1.73) and change in body weight (22.87±6.19 g) in rats fed on diet B were not significantly different (P>0.05) from the control. Compared to the initial values (101.80±3.5 mg/dl), diet B did not cause significant variation (p>0.05) in fasting blood glucose level. The packed cell volume, hemoglobin and red blood cell were significantly increased in rats maintained on diet B. Serum concentrations of triglyceride, low density lipoprotein cholesterol, atherogenic index and serum activities of transaminases were significantly decreased (P
Keywords: Biochemical; Hematology; Lipid; Mixed-spices; Transaminase